Distribution of Clavibacter michiganensis subsp. michiganensis in Various Tomato Production Centers in Sumatra and Java - APRIZAL ZAINAL; ASWALDI ANWAR; UJANG KHAIRUL; . SUDARSONO (Microbiology Indonesia, 2008)
Bacterial canker, caused by Clavibacter michiganensis subsp. michiganensis is a newly introduced disease of tomatoes in Indonesia. Its existence was first officially reported in 2004. The objective of this research was to monitor the existence of C. michiganensis subsp. michiganensis in various tomato production centers in Sumatra and Java. Tomato samples showing symptoms of C. michiganensis subsp. michiganensis infection were collected from various tomato production centers in Sumatera and Java and the causal agents were isolated from these samples. Based on the occurrences of typical symptoms of C. michiganensis subsp. michiganensis infection in tomato, the incidence of suspected C. michiganensis subsp. Michiganensis infection ranged from 1-20%. From a total of 74 tomato plants sampled, 24 bacterial isolates exhibiting similar colony morphology to C. michiganensis subsp. michiganensis were obtained. After various physiological, hypersensitive response, and pathogenicity tests, 18 isolates derived from 14 tomato production centers in eight provinces in Sumatera and Java were identified as C. michiganensis subsp. michiganensis. Although the incidence was still low, results of these experiments further indicated that C. michiganensis subsp. michiganensis existed in Indonesia and had spread in a number of tomato production centers in Sumatra and Java. Positive results of C. michiganensis subsp. Michiganensis identification from suspected tomato samples should be a warning sign for all tomato production stakeholders in Indonesia, especially those responsible in regulating the seed trade, importation, and plant quarantine